Perempuan dan Karir (Telaah Teori Trait And Factor dalam Pengembangan Karir dan Pengambilan Keputusan) - Ani (MUWAZAH : jurnal kajian gender, 2017)
Woman is a figure who often get second class predicate, because deemed not have ability as men. Women are deemed incompetent in their career because of their basic nature. While career is the right of every individual is no exception women, and this does not violate the principle of the creation of women. The direction of women's career development should be tailored to the nature and character of women who are known to be feminine. One of the career development and decision-making efforts is through a career counseling service with Trait and Factor approach carried by Frank Parson. This effort is done so that women can still work in accordance with the nature and nature of the basic that has, so it can complement the role of men.